Pengaruh Keberadaan Komite Manajemen Risiko (Risk Management Committee/RMC) dan Karakteristik Anggota RMC terhadap Pengungkapan Kinerja Lingkungan dan Sosial Perusahaan - Furqani, Nurmeita; Fontanella, Amy; Maryati, Ulfi (Universitas Negeri Padang, 2025)
This study aims to analyze the effect of the existence of a risk management committee (RMC) and the characteristics of RMC members on the disclosure of corporate environmental and social performance. The sample in this study consists of non-financial companies listed on the Indonesia Stock Exchange from 2019-2023 that publish sustainability reports , with a total sample size of 262 and a sub-sample of 81. The sample selection was based on purposive sampling method, and multiple linear regression analysis was used as the main analysis method to test the hypothesis. The results of this study show that the presence of RMC has a positive effect on disclosure of corporate environmental and social performance. Meanwhile, the characteristics of RMC members in terms of educational qualifications and work experience also positively affect the disclosure of corporate environmental and social performance. This study implies the importance of the existence of a risk management committee in the company.